Self-Rated Health Status Based on the Type of Health Insurance: A Socioeconomic Perspective - Minsung Sohn PhD, MPH; Minsoo Jung PhD, MPH; Mankyu Choi PhD, MPH (SAGE Publishing, 2021)
To investigate the effects of public and private health insurance on self-rated health (SRH) status within the National Health Insurance (NHI) system based on socioeconomic status in South Korea. The data were obtained from 10 867 respondents of the Korea Health Panel (2008-2011). We used hierarchical panel logistic regression models to assess the SRH status. We also added the interaction terms of socioeconomic status and type of health insurance as moderators. Medical aid (MA) recipients were 2.10 times more likely to have a low SRH status than those who were covered only by the NHI, even though the healthcare utilization was higher. When the interaction terms were included, those not covered by the NHI and had completed elementary school or less were 16.59 times more likely to have a low SRH status than those covered by the NHI and had earned a college degree or higher. Expanding healthcare coverage to reduce the burden of non-payment and unmet use to improve the health status of MA beneficiaries should be considered. Particularly, the vulnerability of less-educated groups should be focused on.